Enzyme-assisted extraction of insect fat for biodiesel production. (20th June 2019) - Su, Chia-Hung; Nguyen, Hoang Chinh; Bui, Thi Loan; Huang, Deng-Liang
Abstract: Black soldier fly larvae (BSFL), high-fat-containing insects, are a promising non-edible feedstock for biodiesel production. Extracting fat from BSFL biomass for biodiesel production by using traditional methods requires a high amount of solvent, long extraction time, and thermal conditions. To address these limitations, this study proposed an enzyme-assisted extraction method for extracting fat from BSFL biomass for biodiesel production. Different proteases were used to pretreated BSFL biomass prior to the extraction by n-hexane. Among the tested enzymes, Protamex was the most effective for the pretreatment, resulting in the highest fat yield (2.2-fold increase in the fat yield, compared with the extraction without enzymatic treatment). The extraction of insect fat using Protamex-assisted pretreatment was then optimized using response surface methodology (RSM). A four-factor, three-level Box–Behnken design was employed to optimize the factors for the highest fat yield using 27 experimental runs. The optimized conditions were water-to-biomass weight ratio of 4.33:1, enzyme amount of 3.85%, enzymatic treatment temperature of 38.1 °C, and enzymatic treatment time of 4.27 h for a maximum fat yield of 36.09%. The extracted BSFL fat was then used as feedstock for producing biodiesel. Most properties of the synthesized biodiesel met American Society for Testing and Materials (ASTM) specification D6751 and European standard EN 14214. The enzyme-assisted extraction process was then proposed for use in large-scale operations to evaluate its economic feasibility, revealing promising industrial applications. This study suggests that the enzyme-assisted extraction is an efficient method for extracting insect fat, and the extracted fat has potential for use as oil for biodiesel production. Graphical abstract: Image 1 Highlights: Enzyme-assisted extraction was successfully developed to extract fat from insect. The extraction conditions were optimized using response surface methodology. Enzyme-assisted extraction using Protamex and n-hexane improved the fat yield. All properties of black soldier fly larvae biodiesel met the standard EN 14214. The proposed process shows promising industrial applications.